Man at the centre of technology.: a philosophical investigation of anthropological knowledge in man-machine-interfaces - Liggieri, Kevin (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
The paper aims to examine the construction, circulation, and transformation of knowledge about man (anthropological knowledge) in human-technology interaction in the 20th century. The analysis focuses on the prerequisites of the industrial working world and its implicit knowledge about human beings. However, the basis and starting point of technical adaptation is usually ignored: The concepts of “man” and the anthropological knowledge gained experimentally from a anthropocentric designed interface. Based on the concept of an intuitive interface design this problem will be investigated. The questions posed by this article as well as the objectives associated with them open up an interdisciplinary framework between philosophy of technology, philosophical anthropology and history of science given that they not only focus – by means of historical reconstruction – on historical changes in technological developments. They also address the issue of generation and transformation of anthropological knowledge in the definitions and interactions of “man” and “technology”.